2011
DOI: 10.1111/j.1754-9485.2010.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing delay in the diagnosis of pregnancy‐associated breast cancer: How imaging can help us

Abstract: Ultrasonography is recommended for the initial diagnosis of breast symptoms during pregnancy and lactation. A negative study should not delay direct fine needle aspiration of a palpable lesion. Mammography is indicated where initial assessment suggests malignancy. MRI may have a role in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 24 publications
5
44
2
1
Order By: Relevance
“…The other diagnostic delays were due to the patients attributing the disease symptoms to pregnancy (3/8) and lactation (2/8) or the patients not seeking medical care on time (2/8). Our results differ somewhat from those of Taylor et al [7] who reviewed the diagnostic work-up of 22 women with PABC as a part of large population-based national gestational BC study. They identified 5 (22.7%) patients with a diagnostic delay of 4-12 weeks and 4 (18.2%) patients with a diagnostic delay of more than 6 months.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The other diagnostic delays were due to the patients attributing the disease symptoms to pregnancy (3/8) and lactation (2/8) or the patients not seeking medical care on time (2/8). Our results differ somewhat from those of Taylor et al [7] who reviewed the diagnostic work-up of 22 women with PABC as a part of large population-based national gestational BC study. They identified 5 (22.7%) patients with a diagnostic delay of 4-12 weeks and 4 (18.2%) patients with a diagnostic delay of more than 6 months.…”
Section: Discussioncontrasting
confidence: 56%
“…Pregnancy and lactation has significant physiological impacts on breast tissue due to remarkable changes in the hormonal milieu that cause increased breast firmness and nodularity [7,11]. These physiological changes render clinical examination difficult and, as a consequence, reported delays in diagnosis are common and could range up to 10 months [7,8,10,12,13]. According to a comprehensive review by Woo et al [10], the median diagnostic delay in more recent studies was reported as 1 or 2 months, while older studies described much longer periods of delay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature; the Breast Imaging Reporting and Data System (BI-RADS); galactocele accounts for estimated 5% of breast complaints [5]. Accordingly, [12] Delay in galactocelic diagnosis can be relayed to hypertrophy of breast tissue during breast-feeding (lactation) and pregnancy (gravidae) which can spike symptoms [13]. Breast x-ray (mammography) in lactating women often shows dense breast tissue, hence the emphasis on ultrasound as a preferred imaging choice which carries no risk of fetal radiation [14].…”
Section: Discussionmentioning
confidence: 99%
“…With the regard to the latter, further challenges arise in the normal breast during lactation. Namely, tCho is generally detected during that time, but breast cancer can occur during lactation and when it does, it is usually detected late [38]. Overall, it is seen that many different cut-points have been used for tCho in attempts to distinguish cancerous breast lesions from benign breast tissue.…”
Section: In Vivo Mrs For Detecting Breast Cancer: Reliance Upon Totalmentioning
confidence: 99%